The Perspective of HIV Providers in Western Kenya on Provider-Patient Relationships. Issue 6 (3rd June 2018) - Wachira, Juddy; Genberg, Becky; Kafu, Catherine; Koech, Beatrice; Akinyi, Jacqueline; Owino, Regina K.; Laws, Michael Barton; Wilson, Ira B.; Braitstein, Paula
Abstract : Enhancing effective adherence dialogue with HIV patients in an environment that promotes good provider-patient relationships, is key to optimizing the benefits of antiretroviral therapy (ART). The study examines the perspectives of HIV providers in western Kenya on provider-patient relationships. Sixty healthcare providers were sampled using convenience sampling methods from three Academic Model for Providing Access to Healthcare (AMPATH) sites (one urban and two rural). In-depth interviews conducted in either Swahili or English were audio recorded, transcribed, and translated into English. Content analysis was performed after thematic coding. Providers perceived that they had good relationships with most patients, and tended to identify negative patient attributes as the source of poor provider-patient relationships. Providers preferred patients who adhered to treatment guidelines. They did not like patients who challenged their authority, and did not see it as their responsibility to find more effective ways of interacting with patients who they found difficult. Structural barriers to collaborative physician-patient relationships included noncontinuity of relationships, lack of specific appointment times, high provider-patient ratio, and management of provider fatigue and job dissatisfaction. There is need for HIV care programs to identify culturally appropriate interventions to enhance better provider-patient relationship.